PENILAIAN BAHAN BERBAHAYA BERACUN PADA LABORATORIUM RADIOLOGI RSUD BANGIL KABUPATEN PASURUAN - Frans Salesman; Umi Farida (Universitas Airlangga, 2018)
The consequence of activity in hospital is to produce toxic material waste (B3). So, description of B3 in the hospital was needed. The objective of this research was to identify the hazards in each stage in waste management of Liquid Hazardous and Toxic (B3) at Bangil Hospital, Pasuruan. Based on the place , this research was categorized as field research, because it used primary data by interviewing directly to the workforce and conducting risk assessment to the hazard source in the research location. This research was cross-sectional study. The results showed that there were 8 potential hazards, which consist of 3 hazards at the storage stage, 3 hazards at the collection stage, and each 1 hazard at the processing and disposal stage. The hazards proable experienced by laboratory personnel who also serve in the management of liquid waste and also those who operate the IPAL. While the management of B3 liquid waste radiology laboratory conducted by laboratory workers and IPS has 15 potential hazards, including 3 hazards at the storage stage, 6 hazards at the collection stage, 3 hazards at the transport stage and 3 hazards on the temporary storage. Based on the hazard identification at the stage of B3 waste management of Radiology Laboratory at Bangil General Hospital of Pasuruan, there were 15 potential hazards. While at the stage of waste management B3 Liquid Environmental Laboratory in RSUD Bangil Pasuruan, found 8 potential hazards.Keywords : hazardous materials, hospital, radiological laboratory